A Chinese Medicine Compound Alleviates Cisplatin-Induced Acute Kidney Injury via Its Antiapoptosis and Anti-Inflammation Effects in Mice. (29th June 2022) - He, Riming; Liu, Jiahui; Chen, Yulian; Liao, Yijiao; Wang, Yuzhi; Jin, Xiaoming; Li, Zhongtang; Liu, Siqi; Lu, Jiandong; Yang, Shudong
Abstract : Cisplatin, also known as cis-diamine dichloroplatinum (CDDP), is a widely used chemotherapeutic drug. However, its application is limited by the occurrence of serious nephrotoxicity. Currently, no effective therapy is available for combating CDDP-induced acute kidney injury (AKI). In the present study, we investigated the efficacy of Jianpi Yishen Tang (JPYST), a traditional Chinese medicine (TCM) compound commonly used to treat chronic kidney disease, against CDDP-induced AKI. In the CDDP + JPYST group, male mice were pretreated with JPYST (18.35 g/kg/day) for 5 consecutive days before receiving a single dose of CDDP (20 mg/kg), all mice were sacrificed 72 h after the CDDP injection. Results showed that JPYST suppressed CDDP-induced kidney dysfunction and tubular damage scores in the mice. Mechanistically, JPYST treatment attenuated CDDP-induced renal tubular cell apoptosis in AKI mice, as manifested by a marked decreased in TUNEL-positive cell counts, downregulation of the pro-apoptotic proteins Bax, Bad and caspase 3, and upregulation of the antiapoptotic protein Bcl-2 in kidney tissues. Meanwhile, JPYST decreased the expression of inflammatory cytokines TNF- α, IL-1 β, and IL-6 in the serum and renal tissues of mice following CDDP administration. These factors are involved in suppressing the activation of phospho-NF- κ B p65 in tubular epithelial cells. Taken together, these findings demonstrated that JPYST exerts renoprotective effects against CDDP-induced AKI through antiapoptosis and anti-inflammation effects, and these are associated with downregulation of NF- κ B activation. Therefore, JPYST has potential for development of treatment therapies against CDDP-induced AKI.